The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.2337/diabetes.47.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Atypical protein kinase C isozyme zeta mediates carbachol-stimulated insulin secretion in RINm5F cells.

Abstract: Carbachol-stimulated insulin release in the RINm5F cell is associated with elevation of the cytosolic Ca2+ concentration ([Ca2+]i) through mobilization of Ca2+ from thapsigargin-sensitive intracellular stores and with the generation of diacylglycerol (DAG). Thus carbachol activates phospholipase C, and this was thought to be the means by which it stimulates insulin secretion. However, when the elevation of [Ca2+]i was blocked by thapsigargin, the effect of carbachol to stimulate insulin release was unchanged. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 0 publications
1
24
4
Order By: Relevance
“…The lack of a major PKC participation in U-II-effects on spinal cord neurons is further supported by experiments using bisindolylmaleimide I, a specific inhibitor (Toullec et al 1991;Yashpal et al 1995). Some atypical PKC isotypes are PMA-insensitive (Mellor and Parker 1998) and bisindolylmaleimide I fails to block translocation of atypical PKC isozyme zeta in RINm5F cells (Tang and Sharp 1998) Kase et al 1987) are the most specific protein kinase A and protein kinase G inhibitors currently available. Moreover, they are plasma membrane-permeable and have been previously demonstrated to be effective in neurons at the concentrations used in our study (Santschi et al 1999;Hou and Wang 2001).…”
Section: Discussionmentioning
confidence: 96%
“…The lack of a major PKC participation in U-II-effects on spinal cord neurons is further supported by experiments using bisindolylmaleimide I, a specific inhibitor (Toullec et al 1991;Yashpal et al 1995). Some atypical PKC isotypes are PMA-insensitive (Mellor and Parker 1998) and bisindolylmaleimide I fails to block translocation of atypical PKC isozyme zeta in RINm5F cells (Tang and Sharp 1998) Kase et al 1987) are the most specific protein kinase A and protein kinase G inhibitors currently available. Moreover, they are plasma membrane-permeable and have been previously demonstrated to be effective in neurons at the concentrations used in our study (Santschi et al 1999;Hou and Wang 2001).…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that carbachol effectively elevates inositol phosphates in INS-1 cells, which provides evidence that muscarinic receptor signaling is normal in these cells (21). Perhaps INS-1 cells have low or absent levels of expression of the atypical protein kinase C isozyme ( ) that has been implicated in carbachol-stimulated insulin secretion in RIN cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…The above parameters were all measured at the steady state in 11 mM glucose or 11 mM glucose + 100 nM TMX (i.e., after 20 min exposures to TMX). Figure 2 depicts the effects of TMX on [Ca 2+ ] i and 5-HT oscillations in the continued presence of 11 mM glucose and 10 μM bisindolylmaleimide I, a specific broad-range PKC inhibitor (Martiny-Baron et al, 1993;Tang and Sharp, 1998), which did not appear to affect by itself the islet oscillatory activity. In this particular experiment, an irregular activity was observed, with slow oscillations underlying a pattern of high-frequency oscillations both in control and in presence of TMX; this is a pattern that is seen occasionally in islets under physiological conditions and, therefore, unrelated to the presence of bisindolylmaleimide.…”
Section: Resultsmentioning
confidence: 99%
“…Since, at the concentration used, TMX reportedly activates cPKC isoforms only (Ryves et al, 1991), the PKC isoform involved in toxin action is likely to be either PKC-α, PKC-β or both. Indeed, rat pancreatic β-cells and insulinoma cell lines express the cPKC isoforms α and β (Knutson and Hoenig, 1994;Tang and Sharp, 1998;Tian et al, 1996). We are investigating currently whether mouse β-cells express the same cPKC isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation